Wetlands: 3D Mapstory Application to Improve Students’ Learning Outcomes: Effective or Ineffective? - Aristin, Nevy Farista; Saputra, Aswin Nur; Purnomo, Agus; Arini, Dini Noor (FKIP Universitas Lampung, 2025)
Wetlands: 3D Mapstory Application to Improve Students’ Learning Outcomes: Effective or Ineffective?. Objectives: The development of learning media in the era of Education 4.0 can be measured by technological innovation. However, limited time and funds have hindered lecturers and students from various higher education institutions in Indonesia from experiencing direct field practice, especially in the wetlands in South Kalimantan, hailed as one of Indonesia's natural laboratories for wetlands. The development of the Wetlands: 3D Mapstory answers students' conditions to become more familiar with the wetland environment without coming directly to South Kalimantan. The aim is to effectively use the Wetlands: 3D Mapstory to concretize the abstract concept of wetlands to improve students’ learning outcomes. Methods: The research development using the Luther model is limited to the testing stage. It is designed using 3D maps from satellite imagery using ArcGIS and combined with photos and learning materials on wetlands. The validation uses expert judgment on material and media aspects. Effectiveness test using paired sample t-test to analyze effective or ineffective Wetlands: 3D Mapstory Application to improve learning outcomes. Findings: The results show that the Wetlands: 3D Mapstory was developed as an Android-based application. This application was declared feasible and effective for improving student learning outcomes related to developing wetland areas in the Geography Education Study Program at Lambung Mangkurat University. So, the development of Wetlands: 3D Mapstory can fill the gap in learning media geography to improve the quality of lectures. Conclusion: Wetlands: 3D Mapstory Applications are feasible and practical for exploring wetlands in South Kalimantan and enhancing students’ learning outcomes. The implications of the results of this research strengthen and increase the variety of learning media to support learning activities and outcomes in universities. Keywords: wetlands, learning outcomes, 3d mapstory, application, effective.